TINGKAT KEPENTINGAN DAN PELAKSANAAN SARANA WISATA BAGI WISATAWAN MELALUI METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DI OBJEK WISATA PANTAI KETAPING KABUPATEN PADANG PARIAMAN - Fadillah, Ilham Putra; Kasmita, Kasmita; Ferdian, Feri (Journal of Home Economics and Tourism, 2017)
The purpose of research is to determine the level of importance and the implementation of tourist facilities for tourists through the method of Importance Performance Analysis (IPA) in Ketaping Beach Attraction of Padang Pariaman regency. This research consists of 3 indicators of tourism facilities, namely: basic tourism facilities, complementary tourism facilities, tourism support facilities. The type of this research is quantitative descriptive research with survey method. The population in this study are all tourists who visit Ketaping Beach tourist attraction with large population and the number is not known for sure. Sampling technique is non probability sampling, by using incidental sampling. The number of samples in this study amounted to 97 tourists. Data collection using questionnaires based on Likert Scale that has been tested for its validity and reliability. Based on the research result, it is concluded that in general the level of importance and the implementation of tourism facilities for tourists through the method of Importance Performance Analysis of 45.45% of tourists stated that tourism is important and needs to be provided and maintained in the form of hotels and other accommodation, tourist attractions, restaurants, toilets and mushalla.Keywords: Level of Interest, Implementation, Importance Performance Analysis, Ketaping Beach1Prodi D4